2004
DOI: 10.1210/jc.2003-031295
|View full text |Cite
|
Sign up to set email alerts
|

Low Central Nervous System Serotonergic Responsivity Is Associated with the Metabolic Syndrome and Physical Inactivity

Abstract: The metabolic syndrome, recognized by the co-occurrence of general or abdominal obesity, hypertension, dyslipidemia, insulin resistance, and dysglycemia, appears to involve disturbances in metabolism, autonomic function, and health-related behaviors. However, physiological processes linking the components of the metabolic syndrome remain obscure. The current study examined associations of central nervous system serotonergic function with each metabolic syndrome risk variable, the metabolic syndrome, and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 68 publications
7
71
0
2
Order By: Relevance
“…29,30,63 Furthermore, the serotonergic system has been shown to be involved in appetite and weight regulation and to modify the risk for metabolic disorders, as previous studies reported reduced CSF serotonin levels and decreased CNS serotonergic responsivity in MetS and obesity. 26,28 On the other hand, treatment with SSRIs decreases appetite and induces weight loss, 25,64 suggesting that dysregulation in central serotonergic system is important in obesity and MetS.…”
Section: Tph2 and Risk For Mets In MDmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30,63 Furthermore, the serotonergic system has been shown to be involved in appetite and weight regulation and to modify the risk for metabolic disorders, as previous studies reported reduced CSF serotonin levels and decreased CNS serotonergic responsivity in MetS and obesity. 26,28 On the other hand, treatment with SSRIs decreases appetite and induces weight loss, 25,64 suggesting that dysregulation in central serotonergic system is important in obesity and MetS.…”
Section: Tph2 and Risk For Mets In MDmentioning
confidence: 99%
“…In this context, disturbances in brain serotonin system have been suggested to be important in the pathophysiology of both MD and metabolic disorders. [25][26][27] Lower serotonergic activity in the central nervous system (CNS) has been associated with both metabolic disorders 26,28 and MD. 29,30 Furthermore, selective serotonin reuptake inhibitors (SSRIs) have been shown to be successful for the treatment of MD, 31 metabolic disorders 32,33 and presumably for the prevention of cardiovascular morbidity and mortality, 34 emphasizing the importance of the serotonergic system in the pathophysiology of MetS and MD.…”
Section: Introductionmentioning
confidence: 99%
“…36 In humans, reduced central 5-HT responsivity leads to physical inactivity and promotes the development of a metabolic syndrome. 37 A decline in physical activity, in turn, is supposed to underlie middle-age weight gain. 38 Here, we observed decreased motor activity in 5-HTT ko mice already at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin is now recognized as playing a regulatory role in an ever-growing number of autonomic functions (Dedeoglu and Fisher, 1994), cognitive domains (Meneses, 1999), affective, anxiety, and stress-related disorders (Lesch et al, 1996;Shively et al, 1997;Clement and Chapouthier, 1998;Shively et al, 2003), and even metabolic syndromes (Muldoon et al, 2004). As such, the serotonin neural system is a target of pharmacotherapies, steroid hormones, cytokines, neuropeptides, and growth factors, all of which impact the generation and efficacy of serotonin neurotransmission.…”
Section: Introductionmentioning
confidence: 99%